2-Amino-5-oxo-4-(thiophen-2-yl)-5,6,7,8-tetrahydro-4H-chromene-3-carbonitrile - Carren Nyapola; Sizwe J. Zamisa; Eric M. Njogu; Bernard Omondi (IUCrData)
The crystal structure of the title compound, C14H12N2O2S, reveals two symmetrically independent molecules within the asymmetric unit. Each molecule contains a chromenone core attached to a 2-thiophene ring, cyano, and amino groups. The 2-thiophene ring of one of the two molecules in the asymmetric unit was found to be disordered over two positions, with the major component having a site occupancy factor of 0.837 (2). The 2-thiophene ring is nearly orthogonal to the fused 4H-pyran ring, with dihedral angles between the two sets of planes being 89.5 (5) and 89.63 (8)°. Intermolecular hydrogen bonding, involving N—H...N and N—H...O interactions, creates two distinct motifs leading to the formation of a two-dimensional supramolecular network along the crystallographic ac plane.